Pengaruh Kualitas Pelayanan Dan Kualitas produk Terhadap Minat Beli Ulang Dengan Kepuasan Konsumen Sebagai Variabel Intervening Di UD. Rizqi Food Supplier Yogyakarta - Jeffri Nur Syahfudin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effect of service quality and product quality on repurchase intention with consumer satisfaction as an intervening variable at UD. Rizqi Food Supplier Yogyakarta. The impact of Covid-19 has caused a decrease in meat shipments, but extra services and promos during the pandemic have increased interest in repurchasing. After the pandemic, expansion into restaurants and hotels resulted in a significant increase in sales. The research sample consisted of 100 respondents. Data analysis used multiple regression and Sobel's test to test consumer satisfaction as an intervening variable. The results showed that service and product quality had a significant effect on consumer satisfaction and repurchase intention. However, customer satisfaction does not mediate the relationship between service quality and repurchase intention, as well as the relationship between product quality and repurchase intention. Improving the quality of services and products at UD. RizqiFood Supplier is expected to increase consumer satisfaction and encourage repurchasing interest. This is important for company management to retain loyal customers and achieve business success.